Parameter estimation for OEMA models with dual-rate input-output data - Ding Jie; Yin Jun; Zhu Songhao (Proceedings of the 31st Chinese Control Conference, 2012)
This paper deals with the parameter estimation problems of the dual-rate sampled-data systems. The output error models with colored noise are considered as the nature models for systems in industries and thus are taken to model the dual-rate sampled-data systems in this paper. The recursive prediction error method is proposed to estimate the parameters directly from the dual-rate sampled data, and an auxiliary model is employed to estimate the noise-free system output. Simulation is given to test and illustrate the proposed algorithm in the paper.